Disease Calendar of some Parasitic Fungi on Capsicum frutescens in District Shahjahanpur - Pandey*, Adarsh (Journal of Phytology, 2010)
India is the second largest producer of vegetables next only to china. The prime need of our nation is to improve the vegetables, as most of the population of INDIA is vegetarian. Shimla Chilli is one of the major crops, consumed in this country due to its cheaper rate. Several diseases pose a great threat to the cultivation of Capsicum frutescens. These diseases not only reduce the yield of fruits but also deteriorate the quality of fruits. Out of these diseases, fungal diseases are very much hazardous to Capsicum frutescens in this region. During investigation 6 spp. of fungi were recorded on Capsicum frutescens after the survey of different fields and markets in Shahjahanpur. These were viz. Alternaria alternata, Alternaria solani, Curvularia lunata, Choanephora cucurbitarum, Cladosporium oxysporum and Drechslera tetramera. Therefore in the present investigation a disease calendar was prepared to understand the epidemiology of parasitic fungal diseases in Shahjahanpur District. It was found during the study that last week of October to mid December was the best period for the luxuriant growth of parasitic fungi on Capsicum frutescens in District Shahjahanpur, due to low temperature, high humidity and less rainfall.